Complementation of non-tumorigenicity of HPV18-positive cervical carcinoma cells involves differential mRNA expression of cellular genes including potential tumor suppressor genes on chromosome 11q13 - Kehrmann, Angela; Truong, Ha; Repenning, Antje; Boger, Regina; Klein-Hitpass, Ludger; Pascheberg, Ulrich; Beckmann, Alf; Opalka, Bertram; Kleine-Lowinski, Kerstin (Cancer genetics, 2013)
The fusion between human tumorigenic cells and normal human diploid fibroblasts results in non-tumorigenic hybrid cells, suggesting a dominant role for tumor suppressor genes in the generated hybrid cells. After long-term cultivation in vitro, tumorigenic segregants may arise. The loss of tumor suppressor genes on chromosome 11q13 has been postulated to be involved in the induction of the tumorigenic phenotype of human papillomavirus (HPV)18-positive cervical carcinoma cells and their derived tumorigenic hybrid cells after subcutaneous injection in immunocompromised mice. The aim of this study was the identification of novel cellular genes that may contribute to the suppression of the tumorigenic phenotype of non-tumorigenic hybrid cells in vivo. We used cDNA microarray technology to identify differentially expressed cellular genes in tumorigenic HPV18-positive hybrid and parental HeLa cells compared to non-tumorigenic HPV18-positive hybrid cells. We detected several as yet unknown cellular genes that play a role in cell differentiation, cell cycle progression, cell−cell communication, metastasis formation, angiogenesis, antigen presentation, and immune response. Apart from the known differentially expressed genes on 11q13 (e.g., phosphofurin acidic cluster sorting protein 1 (PACS1) and FOS ligand 1 (FOSL1 or Fra-1)), we detected novel differentially expressed cellular genes located within the tumor suppressor gene region (e.g., EGF-containing fibulin-like extracellular matrix protein 2 (EFEMP2) and leucine rich repeat containing 32 (LRRC32) (also known as glycoprotein-A repetitions predominant (GARP)) that may have potential tumor suppressor functions in this model system of non-tumorigenic and tumorigenic HeLa x fibroblast hybrid cells.
Gesehen am 23.04.2021